2014
DOI: 10.1371/journal.pone.0102725
|View full text |Cite
|
Sign up to set email alerts
|

Imidacloprid Alters Foraging and Decreases Bee Avoidance of Predators

Abstract: Concern is growing over the effects of neonicotinoid pesticides, which can impair honey bee cognition. We provide the first demonstration that sublethal concentrations of imidacloprid can harm honey bee decision-making about danger by significantly increasing the probability of a bee visiting a dangerous food source. Apis cerana is a native bee that is an important pollinator of agricultural crops and native plants in Asia. When foraging on nectar containing 40 µg/L (34 ppb) imidacloprid, honey bees (Apis cera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 50 publications
1
42
0
Order By: Relevance
“…Adult worker bees exposed to imidacloprid, clothianidin or thiamethoxam at levels as low as 0.02 ppb would have difficulty performing normal foraging activities. [18][19][20][21][22][23][24] Sub-lethal exposure to acetamiprid, imidacloprid, clothianidin, dinotefuran, fipronil, thiacloprid or thiamethoxam could lead to developmental impairments, including poor colony growth at levels of 2-5 ppb, [25,26] olfactory learning at levels as low as 0.1 mg bee À1 of acetamiprid, [18,[27][28][29] behavioural and cognition-neurological learning at a level of 0.45 ng bee -1 [30][31][32][33] and increasing susceptibility to pathogens at levels of 0.7 ppb of imidacloprid and 0.1 mg kg À1 of thiacloprid. [34][35][36][37] There are several limitations associated with this study.…”
Section: Resultsmentioning
confidence: 99%
“…Adult worker bees exposed to imidacloprid, clothianidin or thiamethoxam at levels as low as 0.02 ppb would have difficulty performing normal foraging activities. [18][19][20][21][22][23][24] Sub-lethal exposure to acetamiprid, imidacloprid, clothianidin, dinotefuran, fipronil, thiacloprid or thiamethoxam could lead to developmental impairments, including poor colony growth at levels of 2-5 ppb, [25,26] olfactory learning at levels as low as 0.1 mg bee À1 of acetamiprid, [18,[27][28][29] behavioural and cognition-neurological learning at a level of 0.45 ng bee -1 [30][31][32][33] and increasing susceptibility to pathogens at levels of 0.7 ppb of imidacloprid and 0.1 mg kg À1 of thiacloprid. [34][35][36][37] There are several limitations associated with this study.…”
Section: Resultsmentioning
confidence: 99%
“…They found that long-term memory, but not short-term or larval survival, was affected by the treatment. Also using Apis cerana in an earlier study, these authors found that trained exposed bees foraged less and had a lower avoidance of predators (i.e., Asian hornet Vespa velutina) (Tan et al 2014). Wright et al (2015) used a choice assay with imidacloprid and thiamethoxam influencing olfactory memory.…”
Section: Experimental (In Vitro) Studiesmentioning
confidence: 99%
“…Some studies suggest that xenobiotics can be harmful to A. cerana cognitive processes. Apis cerana foragers feeding on sugar solution with imidacloprid at 40 μg/L (<0.52 ng/bee) had impaired decision-making and did not avoid nectar with a dangerous hornet predator, unlike controls31. Flumethrin, a pyrethroid commonly used to kill Varroa mites in honey bee colonies, interferes with A. cerana olfactory learning40.…”
mentioning
confidence: 99%